(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
C. attenuata and C. strigipes rearing has been realized in a little grenhouse in arder to enlarge the knowledge about their biology and ethology. The results about the influence of temperature on eggs hatching and on larval development, as well as observations on the adults’ behaviour are reported. The adults of both species have a good predation ability and are highly poliphagous. Cannibalism can happen as a consequence of the lack of other preys.